2020
DOI: 10.3390/jcm9082585
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Cohort Investigation on Zirconia Implants: 5-Year Results

Abstract: Mid-term data on zirconia oral implants is very rare. Therefore, the aim of this prospective clinical investigation was to evaluate the survival rate and the marginal bone loss of a one-piece zirconia implant after five years. Patient-reported outcomes were also recorded. Zirconia implants to support single crowns (SC) or a 3-unit fixed dental prosthesis (FDP) were placed and subsequently restored. After the insertion of the implants, at prosthetic delivery, and after five years, standardized radiographs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Among these aspects, zirconia implants can be considered a viable alternative to titanium implants 9‐11 . Nevertheless, clinical data on zirconia implants are currently based mainly on studies with short observation periods 9‐12 and few studies with medium‐term observation periods reporting promising survival rates after 5 and more years in situ 13‐16 …”
Section: Introductionmentioning
confidence: 99%
“…Among these aspects, zirconia implants can be considered a viable alternative to titanium implants 9‐11 . Nevertheless, clinical data on zirconia implants are currently based mainly on studies with short observation periods 9‐12 and few studies with medium‐term observation periods reporting promising survival rates after 5 and more years in situ 13‐16 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, long-term studies are still limited and mainly focused on one-piece zirconia implant systems (Balmer et al, 2020;Kohal et al, 2020;Roehling et al, 2016). Two recent studies on one-piece zirconia implant have demonstrated a 5-year survival rate between 94.3% and 98.4% Balmer et al, 2020;Kohal et al, 2020). Variability in outcomes could be attributed to the differences in implant design and material, surface treatment, and prosthetic reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent publications on one-piece zirconia implants have reported survival rates of 94.3% and 98.4% after 5 years (Balmer et al, 2020;Kohal et al, 2020).…”
mentioning
confidence: 99%
“…Dental implants are a recognized, safe, and long-lasting method of replacing missing teeth, appreciated by patients and leading to an increase in oral health quality of life [ 1 , 2 , 3 ]. Intensive development of scientific research concerning novel materials used for the production of dental implants and the modifications of their surfaces is currently being observed.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive development of scientific research concerning novel materials used for the production of dental implants and the modifications of their surfaces is currently being observed. The aim of this observation is to accelerate the increase of osteointegration with the patient’s bone [ 3 , 4 ]. The research activity, which is based on the strength and durability of osteointegration, results from the patient’s expectation to expand qualifying indications for dental implantology.…”
Section: Introductionmentioning
confidence: 99%